Circular dichroism of quantum defects in carbon nanotubes created by photocatalytic oxygen functionalization - Finn L. Sebastian; Leon Kaminski; Christoph Bendel; Yohei Yomogida; Yuuya Hosokawa; Han Li; Sebastian Lindenthal; Benjamin S. Flavel; Kazuhiro Yanagi; Jana Zaumseil (Nature Communications)
Abstract Control over the chiroptical properties of low-dimensional semiconductors is a promising route toward next-generation optoelectronics and photonics. With their helical chirality, single-wall carbon nanotubes (SWCNTs) offer a suitable framework for exploring chiral excitonic states. In addition to intrinsic, one-dimensional excitons, the targeted functionalization of SWCNTs with luminescent defects introduces zero-dimensional quantum states that enhance photoluminescence quantum yields and exhibit single-photon emission at room temperature. Here, we demonstrate that these defect states inherit the chirality of the respective SWCNT enantiomer, as evident from near-infrared circular dichroism. This observation is achieved by utilizing photocatalysis for efficient and versatile functionalization of SWCNTs with luminescent oxygen defects. The employed approach, based on anthraquinone derivatives as photocatalysts, is applicable to SWCNTs with different diameters, in aqueous or organic dispersions, with different surfactants, and even enables lateral patterning of defects in SWCNT networks. Low catalyst concentrations and the absence of cytotoxic metals or reactants make this functionalization method highly biocompatible. Introducing luminescent defects with uniform binding configurations in sorted nanotube enantiomers represents a key step toward chirality control of quantum defects in SWCNTs.